Ruin[ed] edge[iness] ruined landscape: Inverting and resurfacing the buried ruin with the scarred landscape - Kruger, Aimee Leah (School of Architecture, Planning and Geomatics, 2018)
This dissertation focuses on the Voortrekker road strip between Salt River Circle and the Black river. It is bounded by the railway lines on the western side, and the Black River and M5 elevated freeway bridge on the eastern side of the strip. The Voortrekker road bridge over the railway line creates a blatant disconnected neighbourly association. The area is currently in a state of decay, plagued by abandoned buildings and crime. Within this focus area I have highlighted 3 key sites of interest, both for their location adjacent to defining natural and man made boundary elements, as well as their state of neglect and ruin or being underutilized. The urban strategy of this project will attempt to uplift and transform this abandoned area by stitching together the two edges of the strip with a pedestrian orientated, contrasting intervention, that inverts the existing ruin, creating a series of relief spaces within this harsh environment. The architectural intervention would address each ruin by inverting them into public space with individual responses and programs, incorporating predominantly a mixed use transport orientated development with housing and rentable spaces above and retail/ market on ground floor. All the sites will use the same technological and structural approach of a light adaptive socially performing structural frame that connects this disconnected, scarred context. The buried, dark and grungy social & material context is thus resurfaced through this light, uplifting, vertical transition. This architectural transition also carefully uses structure and tactility, with walls that grow out of the existing ruined landscape and protect the site. The social user then inhabits this structure and controls or changes their own space to suit their needs within this new vertical spatial framework.